ANALYSIS OF THE POTENTIAL REVENUE OF BUSINESS SERVICE FEES AT THE TRANSPORTATION AND ENVIRONMENT OFFICE OF TOJO UNA-UNA DISTRICT - Handayani, Naniek; Kasim, Muhammad Yunus; Zainudin, Fatlina (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2025)
This study aims to determine and analyze the growth rate and contribution of each type of business service levy, the effectiveness and efficiency of each type of business service levy and the real potential of each type of business service levy. This type of research is quantitative research. The data used is primary data from observations and interviews and secondary data obtained from the Transportation and Environment Agency, covering time series data from 2020 - 2023. Descriptive statistical analysis using the growth rate analysis formula, contribution, effectiveness and efficiency.The results showed mixed performance. The growth of terminal retribution, parking lot retribution and water crossing retribution is